Production of sodium alginate and car freshener - Arcilla, Chester C.; Gallardo, Allen N.; Mara, Joie M.; Sta. Maria, Sherwin A. (Quezon City College of Engineering, 1998)
Products: Sodium alginate, car freshener -- Plant capacity: Sodium alginate - 149419.32 kg, car freshener - 6,018,324 cans -- Plant location: Alamnios, Pangasinan -- Land area: 3,246 sq.m. -- Fixed capital investment: Php 37,672,080.38 -- Total product cost: Php 153,435,856.80 -- Annual sales at maximum production: Php 358,389,036.00 -- Rate of return of investment (ROI): 26.75% -- Payout period: 3.74 years -- Break-even capacity: 5,528.10 kg Sodium Alginate per year
Submitted in partial fulfillment of the requirements in ChE 142 Plant Design.
Keywords: Factories -- Design and construction; Aerogels; Alginates; Sargassum